One-pot synthesis of soft carbon-combined Li2TiSiO5 composites with oxygen vacancies as long life and high rate anodes for lithium-ion batteries. (10th August 2021) - Liu, Yangyang; Li, Bo; Zhang, Mengqi; Zhang, Yupeng; Zhu, He; Xue, Ni; Zhuang, Ji; Zhao, Xiangyan; Tao, Xutang
Highlights: Soft carbon-combined Li2 TiSiO5 is prepared by one-pot sol-gel method. Conductivity of Li2 TiSiO5 anode is effectively improved. Superior cycling performance is achieved for Li2 TiSiO5 /C composite anode. Abstract: Li2 TiSiO5 has been proposed as a practical anode material for lithium-ion batteries with an ideal operational potential of 0.28 V vs. Li/Li + which can fill the voltage region between graphite and Li4 Ti5 O12 . Herein, soft carbon-combined Li2 TiSiO5 composite with extra oxygen vacancies is successfully prepared through a one-pot process. When employed as an anode material for lithium-ion batteries, the novel Li2 TiSiO5 /C composite delivers a high initial discharge capacity of 443 mA h g −1 at a current density of 100 mA g −1, and presents a reversible capacity of 165 mA h g −1 even at 1600 mA g −1 . The long-life cycling is achieved with a capacity retention of 273 mA h g −1 after 1500 cycles under 500 mA g −1 between 0.1 V and 3.0 V. The enhanced cycling stability and prominent rate capability are largely ascribed to the improved conductivities, faster electrochemical reaction kinetics and strong pseudocapacitance effect. This superior lithium-storage performance provides a new opportunity for the further practical applications of novel titanium-based carbon composites as electrode materials in high-power storage devices. Graphical abstract: Image, graphical abstract